Answer:
x(3x-6)=0
Explanation:
x(3x-6)=0
Two solutions were found :
x = 2
x = 0
Step by step solution :
Step 1 :
Step 2 :
Pulling out like terms :
2.1 Pull out like factors :
3x - 6 = 3 • (x - 2)
Equation at the end of step 2 :
3x • (x - 2) = 0
Step 3 :
Theory - Roots of a product :
3.1 A product of several terms equals zero.
When a product of two or more terms equals zero, then at least one of the terms must be zero.
We shall now solve each term = 0 separately
In other words, we are going to solve as many equations as there are terms in the product
Any solution of term = 0 solves product = 0 as well.
Solving a Single Variable Equation :
3.2 Solve : 3x = 0
Divide both sides of the equation by 3:
x = 0
Solving a Single Variable Equation :
3.3 Solve : x-2 = 0
Add 2 to both sides of the equation :
x = 2
Two solutions were found :
x = 2
x = 0